Movement Variability and Perceived Motor Competence in Children with High or Low Risk Willingness in a Virtual Playground - Lise Storli; Håvard Lorås (Children)
Background: The current study explores the relationship between children’s risk willingness and their motor behavior in a virtual playground setting and its association with perceived gross motor competence. Methods: A total of 96 children aged seven to ten participated. They were categorized into high-risk-willingness (HRW) and low-risk-willingness (LRW) groups based on their exploratory behavior and engagement with riskier zones and tasks in the playground. Using whole-body motion capture and virtual reality data, the children’s motor behavior and variability were analyzed alongside self-reported perceived gross motor competence. Results: The results indicated that HRW children displayed significantly greater movement variability, including higher joint movement variability and increased exploration of challenging areas compared to LRW children. HRW children also covered greater distances, moved faster, and exhibited more frequent acceleration changes. Conclusions: These findings suggest that higher risk willingness is associated with greater adaptability and flexibility in motor behavior, aligned with the concept of freeing degrees of freedom. In contrast, no significant differences were found in perceived gross motor competence ratings between HRW and LRW groups. This indicates that perceived motor competence may not directly influence children’s willingness to take risks or their motor behavior in exploratory play. These findings emphasize the importance of studying dynamic interactions between risk-taking, motor behavior, and self-perception to understand the development of adaptive motor skills through risky play.